Jimmy Smith on designing phase II of the Livestock and Fish research program - Smith, Jimmy W. (International Livestock Research Institute, 2015)
Jimmy Smith to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015